2020
DOI: 10.7554/elife.52621
|View full text |Cite
|
Sign up to set email alerts
|

FMRP promotes RNA localization to neuronal projections through interactions between its RGG domain and G-quadruplex RNA sequences

Abstract: The sorting of RNA molecules to subcellular locations facilitates the activity of spatially restricted processes. We have analyzed subcellular transcriptomes of FMRP-null mouse neuronal cells to identify transcripts that depend on FMRP for efficient transport to neurites. We found that these transcripts contain an enrichment of G-quadruplex sequences in their 3′ UTRs, suggesting that FMRP recognizes them to promote RNA localization. We observed similar results in neurons derived from Fragile X Syndrome patient… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 93 publications
(58 citation statements)
references
References 86 publications
2
51
3
Order By: Relevance
“…Dynamic regulation of subcellular RNA localization is critical for biological processes ranging from organismal development to cellular activity 1 7– 6 . While the underlying mechanisms have been found for some transcripts, new aspects of RNA localization regulation continue to arise 7 , 8 . Studies have found that splicing affects RNA localization 9 , 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Dynamic regulation of subcellular RNA localization is critical for biological processes ranging from organismal development to cellular activity 1 7– 6 . While the underlying mechanisms have been found for some transcripts, new aspects of RNA localization regulation continue to arise 7 , 8 . Studies have found that splicing affects RNA localization 9 , 10 .…”
Section: Introductionmentioning
confidence: 99%
“…S10 for FMRP). In this analysis, a shift of the cumulative frequency curve toward the right indicates an up-regulation of targets in the condition of interest, and a leftward shift indicates a down-regulation ( 33 , 34 ). The comparison between FUS targets versus non-target controls shows a minor, albeit significant, right shift (up-regulation) of the cumulative distribution in Ribo- Fus ∆ 14/ ∆ 14 (distance D = 0.05; P = 1.20 × 10 −5 ), while no change was detected in the Ribo- Fus −/− dataset ( D = 0.02; P = 0.26; fig.…”
Section: Resultsmentioning
confidence: 99%
“…Results from knockdown or overexpression studies are often difficult to interpret, as it is challenging to disentangle phenotypes caused by the pleiotropic functions of proteins required for mRNA transport, such as RBPs and motor proteins. For instance, several RBPs involved in neuronal mRNA transport, such as Fragile X Mental Retardation Protein (FMRP) (Dictenberg et al, 2008 ; Goering et al, 2020 ), are also required for nuclear processes (Shah et al, 2020 ), nuclear mRNA export (Zhang et al, 2007 ; Edens et al, 2019 ), and translation regulation (Feng et al, 1997 ), whereas an mRNP-transporting motor protein like kinesin-1 KIF5 transports a variety of cargoes (Twelvetrees et al, 2010 ; Nakajima et al, 2012 ; Barry et al, 2014 ; Heisler et al, 2014 ; Ruane et al, 2016 ; Henrichs et al, 2020 ; Serra-Marques et al, 2020 ). Hence, analyzing the potential role of an RBP or a motor protein in mRNA transport using knockdowns or overexpressions will inevitably affect multiple cellular processes, making the interpretation of results difficult.…”
Section: Value and Limitations Of Past Approachesmentioning
confidence: 99%